Perilaku Antarmuka Berdasarkan Data Beda Tekanan pada Peristiwa Kondensasi Aliran Uap Dengan Pendinginan dari Luar Searah pada Pipa Horisontal Berbasis Domain Waktu - Sukamta Sukamta; Hasan Asy Ari Dwiearto; Sudarja Sudarja (Universitas Muhammadiyah Yogyakarta, 2018)
A two-phase flow pattern experiment on the condensation event of steam flow with external cooling based on the measurement of pressure difference within a horizontal pipe is carried out by varying the superficial velocity. Annulus pipes with inner pipe material made of copper and outer pipe made of galvanized iron (GIP) within an insulation of 10 mm thick were used in this experiment. The length of the pipe is 1.6 meters, outer diameter of 4 inch and inner diameter of 17 mm. The two-phase flow pattern was investigated based on differential pressure fluctuations between the inlet and outlet. To support the observation, flow pattern visualization was performed using a transparent pipe with a diameter of ¾ inch and a length of 1.3 meters connected to the test pipe section. The superficial vapor velocity was carried out from JG = 0.0689 m/s to JG = 1,9117 m/s. The results showed stratified flow patterns for the lowest superficial velocity and also obtained wavy, wavy-slug, and slug. Annular flow patterns can not be observed in this experiment. In general, increasing superficial velocity of steam will cause a significant increase in pressure fluctuations.